2015
DOI: 10.4103/2303-9027.170417
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoscopic ultrasound-guided fine-needle aspiration cytology, viscosity, and carcinoembryonic antigen in pancreatic cyst fluid

Abstract: Due to the advances and increased utility of abdominal cross-sectional imaging, the diagnosis of pancreatic cysts continues to increase. Many endosonographers, pancreatologists, and surgeons consider endoscopic ultrasound (EUS) to be an essential tool in the management of pancreatic cystic lesions (PCLs). EUS can help distinguish between mucinous and nonmucinous lesions and may identify the specific cyst type. EUS achieves these goals by delineating the cyst morphology, identifying high risk stigmata and worri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…The optimal diagnostic approach to PCs remains unclear as there is currently no single test that can reliably differentiate non-neoplastic PCs from those lesions with malignant potential or harboring malignancy. Given the well-recognized limitations of imaging alone [2][3][4], EUS-guided fine-needle aspiration (EUS-FNA) for cytology and cyst fluid analysis is the commonly performed guideline endorsed test for aid with diagnosis and risk stratification [4][5][6][7][8][9][10]. FNA cytology is often limited by the scant cellularity within the cyst fluid [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal diagnostic approach to PCs remains unclear as there is currently no single test that can reliably differentiate non-neoplastic PCs from those lesions with malignant potential or harboring malignancy. Given the well-recognized limitations of imaging alone [2][3][4], EUS-guided fine-needle aspiration (EUS-FNA) for cytology and cyst fluid analysis is the commonly performed guideline endorsed test for aid with diagnosis and risk stratification [4][5][6][7][8][9][10]. FNA cytology is often limited by the scant cellularity within the cyst fluid [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated unique advantages of EUS for the diagnosis of gastrointestinal submucosal tumors. Furthermore, EUS-FNA is the first choice of diagnostic procedure in many diseases, such as pancreatic, gastrointestinal subepithelial, and mediastinal lesions[1-6]. However, the use of a long hard endoscope means that it is much more uncomfortable than general gastroscopy, and cannot be tolerated by some patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, EUS-guided fine needle aspiration (EUS-FNA)[1-6] is a time-consuming procedure associated with pain and discomfort. Painless EUS can reduce patient suffering and thus make patients more likely to accept the examination.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] EUS has been accepted as an important tool in pancreas disease evaluation [13][14][15] and EUS-guided transluminal treatment of PPs is an effective alternative to surgical treatment. [16][17][18][19][20][21][22][23] A CSEMS is primarily used if the contents of the collection are thick, necrotic, or infected, as these collections may not adequately drain through plastic stents.…”
Section: Discussionmentioning
confidence: 99%